EXPLORING THE USE OF CANVA-BASED VISUAL MEDIA IN TEACHING SIMPLE PAST TENSE TO ELEMENTARY STUDENTS - Suciati, Tri Aprilia; Misrita, Misrita; Zulkarnain, Zulkarnain (Journal Compound: Improving the Quality of English Education, 2024)
This study explores the use of Canva-based visual media in teaching the simple past tense to sixth-grade elementary students. Grounded in Vygotsky’s sociocultural theory, the research investigates how visual materials designed by the teacher using Canva can enhance student engagement, facilitate the recognition of verb forms, and support sentence construction. Using a descriptive qualitative approach, the study was conducted across three sessions: one conventional lesson and two sessions integrating Canva-based visuals. Data were collected through classroom observations, student work samples, and teacher reflections. The findings reveal that visual media increased students’ participation, helped them identify regular and irregular past tense forms more accurately, and encouraged them to construct more complete and grammatically correct sentences. Furthermore, the contextual and personalized nature of the visuals supported students in internalizing grammar rules that were previously difficult to grasp. These results suggest that Canva, when used as a scaffolded visual tool, can serve as an effective medium to support grammar instruction for young EFL learners.